2018
DOI: 10.1002/jum.14626
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Urodynamics and Perineal Ultrasonography for the Diagnosis of Mixed Urinary Incontinence in Women

Abstract: Perineal US parameters show good correlations with UDS parameters. Ultrasonography is better tolerated than UDS and provides additional morphologic data. Perineal US could facilitate the diagnosis of urge-predominant MUI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
5
1
Order By: Relevance
“…In our study, the PUVA value of the patients with SUI and MUI during the Valsalva maneuver was statistically different and greater than those with UUI and normal continence. In conclusion, although PUVA measurements with transperineal USG did not determine the type of incontinence, we found that it could detect patients with anatomic defects (23)(24)(25).…”
Section: Discussioncontrasting
confidence: 56%
“…In our study, the PUVA value of the patients with SUI and MUI during the Valsalva maneuver was statistically different and greater than those with UUI and normal continence. In conclusion, although PUVA measurements with transperineal USG did not determine the type of incontinence, we found that it could detect patients with anatomic defects (23)(24)(25).…”
Section: Discussioncontrasting
confidence: 56%
“…The increase in the value of the M-line indicated that the pelvic floor muscles were slack, which increased the probability of bladder and uterine prolapse. In the state of exertion, the dynamic changes of the related angle of the urethra after the surgery would have an impact on urinary control [ 17 ]. Some scholars have suggested that patients with SUI did not need to adjust the abnormal movement of the urethra during surgery [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound evaluation is not standard practice in every setting, but is the source of ongoing clinical evaluation. Transperineal/ translabial ultrasound [18] in women with stress-predominant MUI provides information regarding dynamic posterior urethral angle, dynamic angle of urethral inclination, descent of the bladder neck and dynamic pubourethral distance. In a study of women with MUI, those with urge-predominant MUI had a greater detrusor thickness; and those with equal stress and urge had a greater descent of the bladder neck (p < 0.05).…”
Section: Ultrasound Scan (Transperineal/translabial)mentioning
confidence: 99%